Parenting Patterns and Level of Independence in Preschool Children's Teeth Brushing at Assisi Catholic Kindergarten Medan - Sembiring, Friska; Saragih, Helinida; Elvin Hulu, (Jurnal Midwifery, 2025)
Background Preschool children (golden age periode) are the age where children develop the confidence to explore their independence. One form of independence for preschool children in personal hygiene is brushing their teeth independently. Preschoolers are prone to experience dental caries due to the consumption of sweet foods and low teeth brushing habits, so proper parental parenting is needed to foster independence in maintaining dental hygiene. This research aims to determine parenting patterns and the level of independence in brushing teeth of preschool children at the Assisi Catholic Kindergarten Medan. The method used is a descriptive method with a Cross-Sectional approach. The sample in this study are 35 respondents. The sampling technique is Purposive sampling. The research instrument used is a questionnaire Tiarasukma on parenting patterns and independence in brushing teeth. The research results shows that the majority of parents implemented democratic parenting at 62.9% and the level of independence for preschool children in brushing their teeth reached 74.3%. It is hoped that the results of this research will become learning material for health workers in providing information to parents regarding the implementation of good and correct parenting patterns to help parents more easily teach independent tooth brushing to preschool children.